Analysis of biogenic carbonyl compounds in rainwater by stir bar sorptive extraction technique with chemical derivatization and gas chromatography‐mass spectrometry. Issue 3 (29th December 2016) - Pang, Xiaobing; Lewis, Alastair C.; Shaw, Marvin D.
Abstract : Stir bar sorptive extraction is a powerful technique for the extraction and analysis of organic compounds in aqueous matrices. Carbonyl compounds are ubiquitous components in rainwater, however, it is a major challenge to accurately identify and sensitively quantify carbonyls from rainwater due to the complex matrix. A stir bar sorptive extraction technique was developed to efficiently extract carbonyls from aqueous samples following chemical derivatization by O ‐(2, 3, 4, 5, 6‐pentafluorobenzyl) hydroxylamine hydrochloride. Several commercial stir bars in two sizes were used to simultaneously measure 29 carbonyls in aqueous samples with detection by gas chromatography with mass spectrometry. A 100 mL aqueous sample was extracted by stir bars and the analytes on stir bars were desorbed into a 2 mL solvent solution in an ultrasonic bath. The preconcentration Coefficient for different carbonyls varied between 30 and 45 times. The limits of detection of stir bar sorptive extraction with gas chromatography mass spectrometry for carbonyls (10–30 ng/L) were improved by ten times compared with other methods such as gas chromatography with electron capture detection and stir bar sorptive extraction with high‐performance liquid chromatography and mass spectrometry. The technique was used to determine carbonyls in rainwater samples collected in York, UK, and 20 carbonyl species were quantified including glyoxal, methylglyoxal, isobutenal, 2‐hydroxy ethanal.